A phosphorus-coated hard carbon material and applications in sodium-ion batteries

CN122907623APending Publication Date: 2026-10-13ANHUI LEVINENG POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611213871.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明的目的在于针对现有技术中硬碳负极材料存在的层间距调控不足、比表面积过高、界面结合稳定性差、电子传输能力不足、颗粒致密性和加工性能不佳等问题,提供一种磷包覆的硬碳材料及在钠离子电池中的应用

Benefits of technology

[0036]1.本发明通过生物质芳香碳源、树脂碳源和沥青类致密化碳源的协同碳化作用,使改性硬碳前驱体形成结构较稳定、层间距适度扩大的硬碳基体,有利于钠离子的嵌入和脱嵌,从而提高材料的可逆储钠能力和倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907623A_ABST
    Figure CN122907623A_ABST
Patent Text Reader

Abstract

The application discloses a phosphorus-coated hard carbon material and application thereof in a sodium ion battery, and belongs to the technical field of carbon materials and negative electrode materials of sodium ion batteries. The hard carbon material is prepared from a modified hard carbon precursor, a biomass-based or resin-based carbon source, a phosphorus source, a nitrogen source, a pore-forming agent and deionized water. The modified hard carbon precursor is synergistically constructed from a biomass aromatic carbon source, a resin carbon source, a pitch-based densification carbon source, an oxygen-containing interface regulator, a nitrogen-containing complexing agent, a conductive network regulator, a sacrificial pore-forming salt and a carbonate-type pore regulator. The material has a moderately expanded interlayer spacing, a stable pore structure and a strong interface bonding capacity, and when used as a negative electrode material of a sodium ion battery, can improve sodium storage kinetic performance, a first coulombic efficiency, a rate performance and a cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of carbon materials and sodium-ion battery anode materials, specifically relating to a phosphorus-coated hard carbon material and its application in sodium-ion batteries. Background Technology

[0002] With the development of large-scale energy storage, electric vehicles, distributed energy systems, and low-cost energy storage devices, secondary battery systems are facing higher demands regarding resource reserves, manufacturing costs, safety, and cycle life. Lithium-ion batteries are widely used due to their high energy density and good cycle performance; however, the uneven distribution of lithium resources and significant cost fluctuations limit their further promotion in the field of large-scale energy storage. Sodium-ion batteries, on the other hand, have received widespread attention in recent years due to the abundance and wide distribution of sodium resources, their lower cost, and their similar working mechanism to lithium-ion batteries.

[0003] Anode materials are one of the key factors affecting the capacity, rate performance, initial coulombic efficiency, and cycle life of sodium-ion batteries. Because sodium ions have a larger radius than lithium ions, and traditional graphite materials have small interlayer spacing, it is difficult to achieve efficient sodium ion insertion and extraction. Therefore, graphite-based anode materials are generally unsuitable as high-performance sodium-ion battery anode materials. Hard carbon materials possess a short-range ordered, long-range disordered carbon microcrystalline structure, relatively large interlayer spacing, and certain porosity and defect sites, providing various sodium ion storage sites such as insertion, adsorption, and pore filling. Therefore, they are considered promising anode materials for sodium-ion batteries.

[0004] However, existing hard carbon materials still have the following problems in practical applications: First, the carbon interlayer spacing of some hard carbon materials is not well controlled, and the sodium ion insertion barrier is high, resulting in unsatisfactory rate performance. Second, some hard carbon materials are prepared using strong activation or high porosity methods, which can improve the ion transport rate, but easily lead to excessively high specific surface area, increasing electrolyte side reactions and irreversible formation of solid electrolyte interfacial film, reducing the initial coulombic efficiency. Third, the surface functional groups and interfacial binding sites of hard carbon particles are insufficient, resulting in weak bonding between the subsequent coating layer and the hard carbon matrix, which easily leads to interfacial debonding, coating layer cracking, or local pulverization during long cycling. Fourth, some hard carbon materials have irregular particle morphology, wide particle size distribution, and low tap density, which is not conducive to electrode slurry processing, coating consistency, and volumetric energy density improvement. Fifth, hard carbon materials prepared from a single carbon source usually cannot simultaneously achieve low specific surface area, moderately expanded interlayer spacing, high electronic conductivity, good structural stability, and high tap density.

[0005] To improve the interfacial stability and cycle performance of hard carbon materials, existing technologies typically employ methods such as carbon coating, heteroatom doping, pore structure modulation, or surface modification. Phosphorus, in particular, can regulate the electronic structure and interfacial reaction behavior of hard carbon materials, and is beneficial for forming a more stable interfacial layer, thereby improving the cycle stability of sodium-ion battery anode materials. However, if the interlayer spacing, pore structure, surface functional groups, particle density, and conductive network of the hard carbon matrix itself are not synergistically regulated, simply applying phosphorus coating to the surface of ordinary hard carbon is insufficient to fully address the problems of low initial coulombic efficiency, inadequate rate performance, weak coating layer adhesion, and poor long-term cycle stability in hard carbon anode materials.

[0006] Therefore, it is necessary to provide a new phosphorus-coated hard carbon material and its preparation method, so that the hard carbon matrix has moderately expanded interlayer spacing, low to medium specific surface area, pore structure with micropores and mesopores in synergy, oxygen-containing / nitrogen-containing surface binding sites, high electron transport capacity, regular particle morphology and high tap density before phosphorus coating, and forms a stable interface structure through subsequent phosphorus coating, thereby improving its rate performance, cycle stability, first coulombic efficiency and processing adaptability as a sodium-ion battery anode material. Summary of the Invention

[0007] The purpose of this invention is to address the problems of insufficient interlayer spacing control, excessively high specific surface area, poor interfacial bonding stability, insufficient electron transport capacity, poor particle density, and poor processing performance in existing hard carbon anode materials. This invention provides a phosphorus-coated hard carbon material and its application in sodium-ion batteries. The material uses a modified hard carbon precursor as the core matrix. Through the synergistic effect of biomass aromatic carbon sources, resin carbon sources, pitch-based densifying carbon sources, oxygen-containing interface regulators, nitrogen-containing complexing agents, conductive network regulators, and a non-mesoporous sacrificial pore-forming system, a hard carbon matrix with moderately expanded interlayer spacing, low specific surface area, microporous / mesoporous composite pore structure, and high tap density is constructed. A stable phosphorus coating layer is then formed through phosphorus source composite coating, thereby improving the sodium storage kinetics and cycle stability of the material in sodium-ion batteries.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is: a phosphorus-coated hard carbon material. The hard carbon material is composed of the following components in parts by weight: 70-95 parts of modified hard carbon precursor, 3-20 parts of biomass-based or resin-based carbon source, 1-10 parts of phosphorus source, 1-8 parts of nitrogen source, 0.5-8 parts of pore-forming agent, and 80-300 parts of deionized water.

[0009] By adopting the above technical solution, preferably, the modified hard carbon precursor is composed of the following components in parts by weight: 30-60 parts of biomass aromatic carbon source, 10-35 parts of resin carbon source, 5-25 parts of asphalt-based densifying carbon source, 1-8 parts of oxygen-containing interface regulator, 1-10 parts of nitrogen-containing complexing agent, 0.2-3 parts of conductive network regulator, 5-25 parts of sacrificial pore-forming salt, 1-10 parts of carbonate-type pore regulator, and 100-400 parts of deionized water.

[0010] By adopting the above technical solution, preferably, the biomass-based or resin-based carbon source is one or a combination of two or more of glucose, sucrose, starch, lignin, phenolic resin, and furfural resin.

[0011] By adopting the above technical solution, preferably, the phosphorus source is one or a combination of two or more of phytic acid, ammonium dihydrogen phosphate, ammonium hypophosphite, ammonium polyphosphate, and red phosphorus.

[0012] By adopting the above technical solution, preferably, the nitrogen source is one or a combination of two or more of urea, dicyandiamide, melamine, and polyethyleneimine.

[0013] By adopting the above technical solution, preferably, the pore-forming agent is one or a combination of two or more of ammonium bicarbonate, sodium chloride, potassium chloride, and calcium carbonate.

[0014] By adopting the above technical solution, preferably, the biomass aromatic carbon source is one or a combination of two or more of alkali lignin, sodium lignin sulfonate, tannic acid, coconut shell powder, bamboo powder, starch, and sucrose.

[0015] By adopting the above technical solution, preferably, the resin carbon source is one or a combination of two or more of phenolic resin, furfural resin, epoxy resin, and urea-formaldehyde resin.

[0016] By adopting the above technical solution, preferably, the asphalt-based densifying carbon source is one or a combination of two or more of petroleum asphalt, coal tar pitch, medium-temperature asphalt, and modified asphalt powder.

[0017] By adopting the above technical solution, preferably, the oxygen-containing interface regulator is one or a combination of two or more of citric acid, oxalic acid, tartaric acid, sodium alginate, sodium carboxymethyl cellulose, and tannic acid.

[0018] By adopting the above technical solution, preferably, the nitrogen-containing complexing agent is one or a combination of two or more of urea, dicyandiamide, melamine, polyethyleneimine, and chitosan.

[0019] By adopting the above technical solution, preferably, the conductive network regulator is one or a combination of two or more of conductive carbon black, acetylene black, carbon nanotubes, and graphene microplates.

[0020] By adopting the above technical solution, preferably, the sacrificial pore-forming salt is one or a combination of two or more of sodium chloride, potassium chloride, sodium sulfate, and sodium carbonate.

[0021] By adopting the above technical solution, preferably, the carbonate-type pore conditioner is one or a combination of two or more of calcium carbonate, magnesium carbonate, and ammonium bicarbonate.

[0022] Preferably, the modified hard carbon precursor is prepared by adopting the above technical solution through the following steps:

[0023] S1. By mass, mix 30-60 parts of biomass aromatic carbon source, 10-35 parts of resin carbon source, 5-25 parts of asphalt-based densifying carbon source, 1-8 parts of oxygen-containing interface regulator, 1-10 parts of nitrogen-containing complexing agent, 0.2-3 parts of conductive network regulator, 5-25 parts of sacrificial pore-forming salt, 1-10 parts of carbonate-type pore regulator and 100-400 parts of deionized water, stir and shear disperse at 40-95℃ for 1-6 hours to obtain confined pore-forming composite slurry.

[0024] S2. The confined pore-forming composite slurry obtained in step S1 is spray-dried. The inlet air temperature of the spray drying is 160-220℃, the outlet air temperature is 80-120℃, and the atomizing disc rotation speed is 8000-18000 r / min to obtain composite precursor particles. Then, the composite precursor particles are placed in an air atmosphere and heated to 120-160℃ at a heating rate of 0.5-3℃ / min and held for 1-3 hours, and then heated to 180-260℃ and held for 2-6 hours to obtain stabilized composite particles.

[0025] S3. Place the stabilized composite particles obtained in step S2 in a nitrogen or argon atmosphere, heat them to 350-450℃ at a heating rate of 0.5-5℃ / min and hold for 1-3 hours, then heat them to 550-750℃ and hold for 1-4 hours to obtain pre-carbonized particles; wash the pre-carbonized particles with deionized water and treat them with 0.05-0.5mol / L acid solution for 0.5-4 hours to remove sacrificial pore-forming salts and carbonate-type pore conditioners, then wash them until the pH of the filtrate is 6.5-7.5 and dry them to obtain confined pore-forming carbonized particles.

[0026] S4. Place the confined pore-forming carbonized particles obtained in step S3 in a nitrogen or argon atmosphere and heat-treat them at 850-1150℃ for 1-4 hours to obtain thermally shaped hard carbon particles; disperse the thermally shaped hard carbon particles in an aqueous solution containing hydrogen peroxide and nitrogen-containing components, treat them at 80-160℃ for 2-8 hours, filter, wash, and dry them, and then keep them at 300-550℃ in a nitrogen or argon atmosphere for 0.5-3 hours to obtain a modified hard carbon precursor.

[0027] By adopting the above technical solution, preferably, in step S4, the mass concentration of hydrogen peroxide is 1-10%, the nitrogen-containing component is one or a combination of two or more of urea, dicyandiamide, melamine or polyethyleneimine, and the mass ratio of the nitrogen-containing component to the thermally shaped hard carbon particles is 0.01-0.10:1.

[0028] Preferably, the phosphorus-coated hard carbon material is prepared by the following steps using the above technical solution: 70-95 parts by weight of modified hard carbon precursor, 3-20 parts by weight of biomass-based or resin-based carbon source, 1-10 parts by weight of phosphorus source, 1-8 parts by weight of nitrogen source, 0.5-8 parts by weight of pore-forming agent, and 80-300 parts by weight of deionized water are mixed and ball-milled or dispersed at high speed for 2-8 hours to obtain a phosphorus source composite coating slurry; the phosphorus source composite coating slurry is dried and then placed in a nitrogen or argon atmosphere and heat-treated at 550-850℃ for 1-4 hours to obtain the phosphorus-coated hard carbon material.

[0029] By adopting the above technical solution, preferably, the drying method of the phosphorus source composite coating slurry is one of spray drying, vacuum drying, forced air drying or freeze drying.

[0030] By adopting the above technical solution, preferably, when spray drying is used, the inlet air temperature is 150-210℃, the outlet air temperature is 75-115℃, and the atomizing disc rotation speed is 8000-18000r / min.

[0031] By adopting the above technical solution, preferably, when vacuum drying or forced air drying is used, the drying temperature is 60-120℃ and the drying time is 6-24h.

[0032] A sodium-ion battery negative electrode sheet, the sodium-ion battery negative electrode sheet comprising a current collector and a negative electrode active material layer disposed on at least one side surface of the current collector, the negative electrode active material layer comprising the aforementioned phosphorus-coated hard carbon material, conductive agent and binder; by mass percentage, the negative electrode active material layer comprises 80-96 wt% phosphorus-coated hard carbon material, 1-10 wt% conductive agent and 2-10 wt% binder.

[0033] A sodium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The negative electrode is a sodium-ion battery negative electrode as described above. When the phosphorus-coated hard carbon material is used as the negative electrode material of the sodium-ion battery, it can provide sodium-ion insertion / extraction channels through a hard carbon matrix with a layer spacing of 0.35-0.42 nm, allowing for the insertion / extraction of sodium ions through a 1-50 nm layer spacing. 2 The specific surface area of ​​ / g reduces electrolyte side reactions, enhances the interfacial bonding between the phosphorus coating and the hard carbon matrix through oxygen- or nitrogen-containing functional groups, and improves the cycle stability and rate performance of the anode material through the phosphorus coating.

[0034] This invention uses a modified hard carbon precursor as the core matrix. Through the synergistic carbonization of biomass aromatic carbon sources, resin carbon sources, and pitch-based densifying carbon sources, a hard carbon matrix with short-range order, long-range disorder, and a relatively dense structure is formed. Oxygen-containing interface modifiers and nitrogen-containing complexing agents introduce oxygen- or nitrogen-containing functional groups during stabilization, pre-carbonization, and subsequent surface treatment. Conductive network modifiers improve the electron transport path within the particles. Sacrificial pore-forming salts and carbonate-type pore regulators, after washing and acid treatment, form a microporous / mesoporous composite pore structure, reducing excessively high specific surface area and improving particle structural stability during thermal shaping. Furthermore, the modified hard carbon precursor, together with biomass-based or resin-based carbon sources, phosphorus sources, nitrogen sources, and pore-forming agents, forms a phosphorus source composite coating slurry. After inert atmosphere heat treatment, a stable phosphorus coating layer is formed on the surface of the hard carbon matrix, providing sodium ion insertion / extraction channels within the hard carbon matrix with a 0.35-0.42 nm interlayer spacing. 2 The specific surface area of ​​ / g reduces electrolyte side reactions, enhances the interfacial bonding between the phosphorus coating and the hard carbon matrix through oxygen- or nitrogen-containing functional groups, and inhibits interfacial debonding, coating cracking and local pulverization during long cycling through the phosphorus coating, thereby improving the sodium storage kinetics, cycle stability, rate performance and first coulombic efficiency of the anode material.

[0035] Compared with the prior art, the beneficial effects of the present invention are:

[0036] 1. This invention utilizes the synergistic carbonization effect of biomass aromatic carbon source, resin carbon source and pitch-based densifying carbon source to enable the modified hard carbon precursor to form a hard carbon matrix with a relatively stable structure and moderately expanded interlayer spacing, which is conducive to the insertion and extraction of sodium ions, thereby improving the material's reversible sodium storage capacity and rate performance.

[0037] 2. This invention utilizes the synergistic effect of an oxygen-containing interface regulator, a nitrogen-containing complexing agent, and a phosphorus source composite coating system to form a stable phosphorus-containing composite interface structure on the surface of a hard carbon matrix. This enhances the bonding stability between the phosphorus coating layer and the hard carbon matrix, reduces interface debonding, coating layer cracking, and localized pulverization during cycling, thereby improving cycling stability.

[0038] 3. This invention, through the combination of conductive network regulators, sacrificial pore-forming salts and carbonate-type pore regulators, constructs suitable electron transport channels and pore structures while maintaining particle regularity and good processing performance, reducing the occurrence of excessive side reactions, and enabling the negative electrode material to have good initial coulombic efficiency, capacity utilization and electrode processing adaptability. Attached Figure Description

[0039] Figure 1 This is a SEM image of the modified hard carbon precursor 1 prepared in Preparation Example 1 of the present invention.

[0040] Figure 2This is a SEM image of the phosphorus-coated hard carbon material 1 prepared in Example 1 of the present invention.

[0041] Figure 3 This is the XPS full spectrum of the phosphorus-coated hard carbon material 1 prepared in Example 1 of the present invention.

[0042] Figure 4 This is a photograph of the phosphorus-coated hard carbon material negative electrode sheet prepared in Example 1 of the present invention. Detailed Implementation

[0043] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Preparation Example 1

[0045] Preparation of modified hard carbon precursors:

[0046] 1. Raw material components by weight:

[0047] Aromatic carbon source from biomass, selected from 45 parts of alkali lignin.

[0048] The carbon source for the resin was selected from 22 parts of phenolic resin.

[0049] The carbon source for densification of asphalt was selected from 15 parts of medium-temperature asphalt powder.

[0050] Oxygen-containing interface regulator, selected from: 4 parts of citric acid.

[0051] Nitrogen-containing complexing agent, selected from: 6 parts of urea.

[0052] Conductive network modifier, selected from: 1 part of carbon nanotubes.

[0053] Sacrificial pore-forming salt, selected from: 15 parts of sodium chloride.

[0054] Carbonate-type pore conditioner, selected from: 5 parts of calcium carbonate.

[0055] 250 portions of deionized water.

[0056] 2. Preparation method:

[0057] S1. Weigh 250 parts of deionized water according to the above mass ratio and add it to the mixing tank. Add 4 parts of citric acid, 6 parts of urea and 15 parts of sodium chloride in sequence at a stirring speed of 500 r / min and stir for 30 min to disperse it evenly. Then add 45 parts of alkali lignin, 22 parts of phenolic resin, 15 parts of medium-temperature asphalt powder, 1 part of carbon nanotubes and 5 parts of calcium carbonate. Raise the system temperature to 80℃ and stir at a stirring speed of 800 r / min for 1 h. Then use a high-speed shear disperser to shear disperse at 9000 r / min for 2 h to obtain a uniformly dispersed confined pore-forming composite slurry.

[0058] S2. The confined pore-forming composite slurry obtained in step S1 is spray-dried. The inlet air temperature of the spray dryer is 190℃, the outlet air temperature is 95℃, the atomizing disc speed is 12000r / min, and the feed rate is 20mL / min. Composite precursor particles are collected. Then, the obtained composite precursor particles are placed in an air-atmosphere forced-air drying oven and heated to 140℃ at a heating rate of 1℃ / min and held for 2h. Then, the temperature is increased to 220℃ at a heating rate of 1℃ / min and held for 4h to allow the phenolic resin, medium-temperature asphalt powder, and biomass aromatic carbon source to undergo pre-crosslinking and stabilization treatment. After cooling to room temperature, stabilized composite particles are obtained.

[0059] S3. Place the stabilized composite particles obtained in step S2 in a tube furnace, and purge with nitrogen as a protective atmosphere at a flow rate of 300 mL / min. Increase the temperature to 400℃ at a rate of 2℃ / min and hold for 2 hours. Then increase the temperature to 650℃ at a rate of 3℃ / min and hold for 3 hours. After holding, allow the particles to cool naturally to room temperature in a nitrogen atmosphere to obtain pre-carbonized particles. Wash the obtained pre-carbonized particles three times with deionized water at a mass ratio of 1:20 for each wash, with a stirring time of 30 minutes per wash. Then, treat the washed pre-carbonized particles in 0.2 mol / L hydrochloric acid solution for 2 hours at a mass ratio of 1:15 to remove sacrificial pore-forming salts and carbonate-type pore conditioners. After acid treatment, filter the solution and wash repeatedly with deionized water until the pH of the filtrate reaches 7.0. Then, dry the filtrate in a 90℃ forced-air drying oven for 12 hours to obtain confined pore-forming carbonized particles.

[0060] S4. Place the confined pore-forming carbonized particles obtained in step S3 into a tube furnace, introduce nitrogen as a protective atmosphere, and the nitrogen flow rate is 300 mL / min; heat to 1000℃ at a heating rate of 3℃ / min and hold for 3 hours. After the holding period, allow to cool naturally to room temperature in a nitrogen atmosphere to obtain thermally shaped hard carbon particles. Subsequently, 100 parts of thermally shaped hard carbon particles were dispersed in 500 parts of an aqueous solution containing hydrogen peroxide and a nitrogen-containing component. The mass concentration of hydrogen peroxide in the aqueous solution was 5%, and the nitrogen-containing component was urea. The mass ratio of urea to thermally shaped hard carbon particles was 0.05:1. The dispersion system was transferred to a hydrothermal reactor and treated at 120°C for 5 hours. After treatment, the mixture was cooled to room temperature, filtered, and washed three times with deionized water. Then, it was dried at 90°C for 12 hours. The dried particles were placed in a tube furnace again, and nitrogen was introduced as a protective atmosphere at a flow rate of 300 mL / min. The temperature was increased to 450°C at a rate of 2°C / min and held for 2 hours. After holding, the mixture was naturally cooled to room temperature in a nitrogen atmosphere to obtain modified hard carbon precursor 1.

[0061] SEM images of modified hard carbon precursor 1 are shown below. Figure 1 As shown, the particles exhibit a near-spherical or sub-spherical morphology at the micron level, with some degree of accumulation and slight agglomeration, indicating the formation of a relatively regular secondary particle structure after spray drying. The particle surface is relatively rough, with visible small protrusions, pits, and local pores, indicating that the sacrificial pore-forming salt and carbonate-type pore regulator formed a porous structure on the particle surface and inside after water washing and acid treatment. Some particle surfaces are covered with fine debris and a small amount of strip-like structures, which are related to the conductive network regulator and carbonaceous fragments formed during carbonization. This indicates that the modified hard carbon precursor 1 possesses both good particle regularity and surface active structure, which is beneficial for the uniform adhesion of the subsequent phosphorus source composite coating slurry to the particle surface and helps improve the processing dispersion and interfacial bonding stability of the anode material.

[0062] Preparation Example 2

[0063] In this preparation example, modified hard carbon precursor 2 was prepared by referring to the preparation method of preparation example 1, except that 45 parts of alkali lignin were replaced with 45 parts of sodium lignin sulfonate, and the rest remained the same as in preparation example 1.

[0064] Preparation Example 3

[0065] In this preparation example, modified hard carbon precursor 3 was prepared by referring to the preparation method of Preparation Example 1, except that 22 parts of phenolic resin were replaced with 22 parts of furfural resin, and the rest remained the same as in Preparation Example 1.

[0066] Preparation Example 4

[0067] In this preparation example, a modified hard carbon precursor 4 was prepared. The preparation method of Preparation Example 1 was followed, except that 1 part of carbon nanotubes was replaced with 1 part of graphene microsheets, and the rest remained the same as in Preparation Example 1.

[0068] Comparative Preparation Example 1

[0069] In this comparative preparation example, a comparative modified hard carbon precursor 1 was prepared. The preparation method of Preparation Example 1 was followed, except that 15 parts of medium-temperature pitch powder were replaced with 15 parts of alkali lignin, and the rest remained the same as in Preparation Example 1.

[0070] Comparative Preparation Example 2

[0071] In this comparative preparation example, a comparative modified hard carbon precursor 2 was prepared. The preparation method of Preparation Example 1 was followed, except that 4 parts of citric acid were replaced with 4 parts of deionized water, and the rest remained the same as in Preparation Example 1.

[0072] Comparative preparation example 3

[0073] In this comparative preparation example, a comparative modified hard carbon precursor 3 was prepared. The preparation method of Preparation Example 1 was followed, except that 6 parts of urea were replaced with 6 parts of deionized water, and the rest remained the same as in Preparation Example 1.

[0074] Comparative preparation example 4

[0075] In this comparative preparation example, a comparative modified hard carbon precursor 4 was prepared. The preparation method of Preparation Example 1 was followed, except that 1 part of carbon nanotubes was replaced with 1 part of deionized water, and the rest remained the same as in Preparation Example 1.

[0076] Comparative preparation example 5

[0077] In this comparative preparation example, a comparative modified hard carbon precursor 5 was prepared. The preparation method of Preparation Example 1 was followed, except that 15 parts of sodium chloride and 5 parts of calcium carbonate were replaced with 20 parts of deionized water, and the rest remained the same as in Preparation Example 1.

[0078] Comparative preparation example 6

[0079] In this comparative preparation example, a comparative modified hard carbon precursor 6 was prepared. The preparation method of Preparation Example 1 was followed, except that 1 part of carbon nanotubes was replaced with 1 part of silica micropowder, and the rest remained the same as in Preparation Example 1.

[0080] Example 1

[0081] Preparation of a phosphorus-coated hard carbon material:

[0082] 1. Raw material components by weight:

[0083] The modified hard carbon precursor was selected from 85 parts of the modified hard carbon precursor 1 obtained in Preparation Example 1.

[0084] Biomass-based or resin-based carbon source, selected from: 8 parts of glucose.

[0085] Phosphorus source: 4 parts of ammonium dihydrogen phosphate.

[0086] Nitrogen source: 3 parts of melamine.

[0087] Pore-forming agent, selected from: 2 parts of ammonium bicarbonate.

[0088] 160 portions of deionized water.

[0089] 2. Preparation method:

[0090] S1. Weigh 160 parts of deionized water according to the above-mentioned mass ratio and add it to a ball mill jar. Add 4 parts of ammonium dihydrogen phosphate, 3 parts of melamine and 8 parts of glucose in sequence at a stirring speed of 300 r / min. Stir for 30 min to fully dissolve or disperse the phosphorus source, nitrogen source and biomass-based carbon source in the deionized water to obtain a phosphorus- and nitrogen-containing mixed solution. Then add 85 parts of the modified hard carbon precursor 1 prepared in Preparation Example 1 and 2 parts of ammonium bicarbonate to the phosphorus- and nitrogen-containing mixed solution and continue stirring for 30 min to obtain the initial mixed slurry.

[0091] S2. The initial mixed slurry obtained in step S1 is ball-milled and dispersed. The ball milling medium is zirconia balls, and the mass ratio of zirconia balls to the initial mixed slurry is 3:1. The ball milling speed is 400 r / min, and the ball milling time is 4 h. During the ball milling process, the slurry temperature is controlled not to exceed 45℃, resulting in a uniformly dispersed phosphorus source composite coated slurry. In the phosphorus source composite coated slurry, ammonium dihydrogen phosphate, melamine, and glucose are uniformly adsorbed on the surface and adjacent areas of the pores of the modified hard carbon precursor 1, while ammonium bicarbonate is dispersed in the interparticle spaces and the coating layer precursor region.

[0092] S3. The phosphorus source composite coating slurry obtained in step S2 is spray-dried. The inlet air temperature is 180℃, the outlet air temperature is 90℃, the atomizing disc speed is 12000 r / min, and the feed rate is 18 mL / min. The phosphorus and nitrogen-containing coated precursor particles are collected. The obtained phosphorus and nitrogen-containing coated precursor particles are placed in an 80℃ forced-air drying oven for 6 hours to remove residual moisture from the particles.

[0093] S4. Place the phosphorus- and nitrogen-containing coated precursor particles obtained in step S3 into a tube furnace, and introduce nitrogen as a protective atmosphere at a flow rate of 300 mL / min. Increase the temperature to 300°C at a rate of 2°C / min and hold for 1 hour to allow glucose to undergo dehydration and condensation, and to cause ammonium bicarbonate to decompose and release gas. Then, increase the temperature to 700°C at a rate of 3°C / min and hold for 2 hours to convert glucose into a coated carbon layer. This allows ammonium dihydrogen phosphate and melamine to participate in the formation of the phosphorus- and nitrogen-containing interface structure, forming a phosphorus coating layer on the surface of the modified hard carbon precursor 1. After the holding period, allow it to cool naturally to room temperature in a nitrogen atmosphere to obtain the heat-treated product.

[0094] S5. The heat-treated product obtained in step S4 is washed twice in deionized water. The mass ratio of the heat-treated product to the deionized water is 1:15 each time, and the stirring and washing time is 20 min each time. After filtration, the filter cake is placed in a 90℃ forced-air drying oven and dried for 12 h. Then, it is sieved with a 200-mesh sieve to obtain phosphorus-coated hard carbon material 1.

[0095] SEM images of phosphorus-coated hard carbon material 1 are shown below. Figure 2 As shown, the particles exhibit a micron-sized, near-spherical or quasi-spherical morphology, with some aggregation and slight agglomeration between them. The particle size distribution is relatively concentrated but still retains some variation. The particle surface is relatively rough, with small protrusions, pits, pores, and a small amount of attached debris. This indicates that after treatment with the phosphorus-source composite coating slurry and inert atmosphere heat treatment, the carbon coating layer formed by glucose carbonization, together with the phosphorus and nitrogen sources, creates a relatively rough phosphorus-containing coating interface on the particle surface. Simultaneously, the thermal decomposition of ammonium bicarbonate releases gas, forming localized porous structures on the particle surface and near the surface. This morphology indicates that the phosphorus-coated hard carbon material 1 possesses both good particle regularity and surface active structure, which is beneficial for electrolyte wetting, sodium ion transport, and dispersion in the negative electrode slurry processing.

[0096] XPS full spectrum of phosphorus-coated hard carbon material 1 is as follows: Figure 3 As shown in the figure, the surface of the phosphorus-coated hard carbon material 1 mainly exhibits C, O, N, and P related signals, with the C1s peak being the strongest, indicating that the material body is still dominated by a hard carbon matrix and a carbonized coating layer. The O1s signal indicates that the material surface retains certain oxygen-containing functional groups or phosphorus-oxygen structures, while the N1s signal originates from the nitrogen-containing interface structure formed after heat treatment of melamine and nitrogen-containing components in the precursor. P2p and P2s signals are visible in the low binding energy region, indicating that phosphorus has been successfully introduced into the surface of the phosphorus-coated hard carbon material 1. Slight baseline fluctuations and weak impurity signals are present in the spectra, consistent with the surface testing characteristics of carbon materials. These results indicate that the surface of the phosphorus-coated hard carbon material 1 forms a composite interface structure containing oxygen, nitrogen, and phosphorus, which is beneficial for enhancing the interfacial bonding between the phosphorus coating layer and the hard carbon matrix, and improving its interfacial stability as a sodium-ion battery anode material.

[0097] Examples 2-4

[0098] The preparation of a phosphorus-coated hard carbon material is carried out according to the preparation method of Example 1, except that the modified hard carbon precursor 1 is replaced by modified hard carbon precursor 2 to modified hard carbon precursor 4 in sequence, and the rest is the same as in Example 1.

[0099] Comparative Examples 1-6

[0100] The preparation of a phosphorus-coated hard carbon material is carried out according to the preparation method of Example 1, except that the modified hard carbon precursor 1 is replaced sequentially with comparative modified hard carbon precursor 1-comparative modified hard carbon precursor 6, and the rest is the same as in Example 1.

[0101] Comparative Example 7

[0102] The preparation of a phosphorus-coated hard carbon material is carried out according to the preparation method of Example 1, except that the modified hard carbon precursor 1 is replaced with commercially available ordinary hard carbon powder, and the rest is the same as in Example 1.

[0103] Commercially available hard toner was purchased from Shandong Taihe Technology Co., Ltd., HC-300.

[0104] Performance testing:

[0105] 1. Powder Conductivity Test: The powder conductivity of phosphorus-coated hard carbon material was tested using a powder resistivity tester. 1.00 g of the sample was weighed and placed in a mold, a pressure of 20 MPa was applied and held for 60 seconds to allow the powder to form a stable compacted body. The resistance value of the sample was then measured under 20 MPa pressure. The powder conductivity was calculated based on the thickness, cross-sectional area, and resistance value of the compacted body. The data are shown in Table 1.

[0106] 2. Negative Electrode Preparation Method: The phosphorus-coated hard carbon materials obtained in Examples 1-4 and Comparative Examples 1-7 were used as negative electrode active materials. Phosphorus-coated hard carbon materials, conductive carbon black Super P, and polyvinylidene fluoride were weighed at a mass ratio of 90:5:5 and added to N-methylpyrrolidone for mixing. The mixture was stirred at 1000 rpm for 30 min using a planetary mixer, followed by stirring at 2000 rpm for 60 min to obtain a uniform negative electrode slurry. The obtained negative electrode slurry was coated onto the surface of copper foil, with a wet film thickness of 120 μm. After coating, it was dried in an 80℃ forced-air drying oven for 2 h, and then transferred to a 120℃ vacuum drying oven for 12 h. The dried electrode was then rolled at a pressure of 5 MPa and subsequently punched into circular pieces with a diameter of 12 mm to obtain the sodium-ion battery negative electrode. The negative electrode active material loading in the obtained negative electrode was 1.20 mg / cm³. 2 ,like Figure 4 As shown.

[0107] Using the aforementioned sodium-ion battery negative electrode as the working electrode, a metallic sodium sheet as the counter electrode and reference electrode, and a glass fiber membrane as the separator, a CR2032 coin cell was assembled. The electrolyte was a 1 mol / L NaPF6 EC / DEC / PC mixed solution, with a volume ratio of EC, DEC, and PC of 1:1:1, and 5 wt% fluoroethylene carbonate was added. The electrolyte volume added to each coin cell was 80 μL. Battery assembly was carried out in an argon-filled glove box, with the water content and oxygen content controlled at 0.1 ppm. After assembly, the coin cells were allowed to stand at 25°C for 12 h before electrochemical performance testing.

[0108] 2.1 The initial charge-discharge performance of coin cell half-cells was tested using a battery testing system. The test temperature was 25℃, the voltage window was 0.01V-2.50V, and the current density was 30mA / g. During the test, the cells were first discharged to 0.01V, then charged to 2.50V, and the initial coulombic efficiency was recorded. The initial coulombic efficiency was calculated using the following formula:

[0109] The initial coulombic efficiency = initial charge specific capacity / initial discharge specific capacity × 100%, as shown in Table 1.

[0110] 2.2 Cycle Performance Test: The cycle stability of the coin cell half-cell was tested using a battery testing system. The test temperature was 25℃, and the voltage window was 0.01V-2.50V. The battery was first subjected to 3 activation cycles at a current density of 30mA / g, followed by 200 cycles at a current density of 300mA / g. The specific capacity at the 4th and 200th cycles was recorded, and the capacity retention rate was calculated using the following formula: Capacity retention rate = Specific capacity at 200th cycle / Specific capacity at 4th cycle × 100%. The data are shown in Table 1.

[0111] Table 1 Example 1 3.62 373.8 326.8 87.4 93.7 Example 2 3.2 371.6 323.3 87 93 Example 3 3.08 376.2 325.4 86.5 92.6 Example 4 3.94 372.9 324.4 87 92.8 Comparative Example 1 1.82 390.6 315.6 80.8 84.5 Comparative Example 2 2.35 378.4 314.8 83.2 86.4 Comparative Example 3 2.23 374.5 313.8 83.8 86.9 Comparative Example 4 1.12 368.8 306.5 83.1 82.3 Comparative Example 5 2.15 340.2 299 87.9 85.3 Comparative Example 6 0.86 360.5 294.9 81.8 79.3 Comparative Example 7 1.45 355.8 290.9 81.8 78.9

[0112] Table 1 shows that the overall performance of the examples is superior to that of the comparative examples, indicating that the modified hard carbon precursor, with further phosphorus coating, achieves a synergistic improvement in electron transport, reversible sodium storage capacity, initial coulombic efficiency, and cycle stability. Example 1 exhibits the best overall performance, demonstrating that the combination of alkali lignin, phenolic resin, medium-temperature pitch powder, citric acid, urea, carbon nanotubes, sacrificial pore-forming salt, and carbonate-type pore regulator effectively balances particle density, appropriate pore structure, interfacial active sites, and conductive network. Although Examples 2, 3, and 4 change the biomass aromatic carbon source, resin carbon source, or conductive network regulator, they still maintain good overall performance, indicating that the technology system has a certain degree of adaptability. In contrast, Comparative Example 1, despite an increase in apparent discharge capacity due to the removal of pitch-based densified carbon sources, exhibited greater irreversible capacity loss, resulting in decreased initial coulombic efficiency and cycle retention. Comparative Examples 2 and 3, lacking either oxygen-containing interface modifiers or nitrogen-containing complexing agents, weakened the interfacial bonding and stability between the phosphorus coating layer and the hard carbon matrix. Comparative Example 4, lacking effective conductive network modifiers, showed significantly deteriorated powder conductivity and cycle stability. Comparative Example 5, lacking sacrificial pore-forming salts and carbonate-type pore modifiers, suffered from insufficient pore structure, affecting sodium storage activity and capacity utilization. Comparative Example 6, using silica micropowder instead of carbon nanotubes, experienced hindered electron transport, and the inert inorganic phase was detrimental to reversible sodium storage. Comparative Example 7, using commercially available ordinary hard carbon powder, exhibited the lowest overall performance, indicating that phosphorus coating alone could not compensate for the deficiencies of ordinary hard carbon matrices in terms of interlayer spacing, pore structure, interfacial bonding sites, and conductive network. This demonstrates that the synergistic design of the modified hard carbon precursor and phosphorus coating structure in this invention can effectively improve the comprehensive electrochemical performance of sodium-ion battery anode materials.

[0113] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A phosphorus-coated hard carbon material, characterized in that, The hard carbon material is composed of the following components by weight: 70-95 parts of modified hard carbon precursor, 3-20 parts of biomass-based or resin-based carbon source, 1-10 parts of phosphorus source, 1-8 parts of nitrogen source, 0.5-8 parts of pore-forming agent, and 80-300 parts of deionized water. The modified hard carbon precursor is composed of the following components in parts by weight: 30-60 parts of biomass aromatic carbon source, 10-35 parts of resin carbon source, 5-25 parts of asphalt-based densifying carbon source, 1-8 parts of oxygen-containing interface regulator, 1-10 parts of nitrogen-containing complexing agent, 0.2-3 parts of conductive network regulator, 5-25 parts of sacrificial pore-forming salt, 1-10 parts of carbonate-type pore regulator, and 100-400 parts of deionized water.

2. The phosphorus-coated hard carbon material according to claim 1, characterized in that, The biomass-based or resin-based carbon source is one or a combination of two or more of glucose, sucrose, starch, lignin, phenolic resin, and furfural resin. The phosphorus source is one or a combination of two or more of phytic acid, ammonium dihydrogen phosphate, ammonium hypophosphite, ammonium polyphosphate, and red phosphorus. The nitrogen source is one or a combination of two or more of urea, dicyandiamide, melamine, and polyethyleneimine; The pore-forming agent is one or a combination of two or more of ammonium bicarbonate, sodium chloride, potassium chloride, and calcium carbonate.

3. The phosphorus-coated hard carbon material according to claim 1, characterized in that, The biomass aromatic carbon source is one or a combination of two or more of the following: alkali lignin, sodium lignin sulfonate, tannic acid, coconut shell powder, bamboo powder, starch, and sucrose. The resin carbon source is one or a combination of two or more of phenolic resin, furfural resin, epoxy resin, and urea-formaldehyde resin. The asphalt-based densifying carbon source is one or a combination of two or more of petroleum asphalt, coal tar pitch, medium-temperature asphalt, and modified asphalt powder.

4. The phosphorus-coated hard carbon material according to claim 1, characterized in that, The oxygen-containing interface regulator is one or a combination of two or more of the following: citric acid, oxalic acid, tartaric acid, sodium alginate, sodium carboxymethyl cellulose, and tannic acid. The nitrogen-containing complexing agent is one or a combination of two or more of urea, dicyandiamide, melamine, polyethyleneimine, and chitosan; The conductive network modifier is one or a combination of two or more of the following: conductive carbon black, acetylene black, carbon nanotubes, and graphene microplates. The sacrificial pore-forming salt is one or a combination of two or more of sodium chloride, potassium chloride, sodium sulfate, and sodium carbonate; The carbonate-type pore conditioner is one or a combination of two or more of calcium carbonate, magnesium carbonate, and ammonium bicarbonate.

5. The phosphorus-coated hard carbon material according to claim 1, characterized in that, The modified hard carbon precursor was prepared by the following steps: S1. By mass, the biomass aromatic carbon source, resin carbon source, asphalt densifying carbon source, oxygen-containing interface regulator, nitrogen-containing complexing agent, conductive network regulator, sacrificial pore-forming salt, carbonate pore regulator and deionized water are mixed, stirred and sheared at 40-95℃ for 1-6 hours to obtain confined pore-forming composite slurry. S2. The confined pore-forming composite slurry obtained in step S1 is spray-dried. The inlet air temperature of the spray drying is 160-220℃, the outlet air temperature is 80-120℃, and the rotation speed of the atomizing disc is 8000-18000 r / min to obtain composite precursor particles. Then, the composite precursor particles are placed in an air atmosphere and heated to 120-160℃ at a heating rate of 0.5-3℃ / min and held for 1-3 hours, and then heated to 180-260℃ and held for 2-6 hours to obtain stabilized composite particles. S3. Place the stabilized composite particles obtained in step S2 in a nitrogen or argon atmosphere, heat them to 350-450℃ at a heating rate of 0.5-5℃ / min and hold for 1-3 hours, then heat them to 550-750℃ and hold for 1-4 hours to obtain pre-carbonized particles; wash the pre-carbonized particles with deionized water and treat them with 0.05-0.5mol / L acid solution for 0.5-4 hours to remove sacrificial pore-forming salts and carbonate-type pore conditioners, then wash them until the pH of the filtrate is 6.5-7.5 and dry them to obtain confined pore-forming carbonized particles; S4. Place the confined pore-forming carbonized particles obtained in step S3 in a nitrogen or argon atmosphere and heat-treat them at 850-1150℃ for 1-4 hours to obtain thermally shaped hard carbon particles; disperse the thermally shaped hard carbon particles in an aqueous solution containing hydrogen peroxide and nitrogen-containing components, treat them at 80-160℃ for 2-8 hours, filter, wash, and dry them, and then keep them at 300-550℃ in a nitrogen or argon atmosphere for 0.5-3 hours to obtain a modified hard carbon precursor.

6. The phosphorus-coated hard carbon material according to claim 5, characterized in that, In step S4, the mass concentration of hydrogen peroxide is 1-10%, the nitrogen-containing component is one or a combination of two or more of urea, dicyandiamide, melamine or polyethyleneimine, and the mass ratio of the nitrogen-containing component to the thermally shaped hard carbon particles is 0.01-0.10:

1.

7. The phosphorus-coated hard carbon material according to claim 1, characterized in that, The phosphorus-coated hard carbon material is prepared by the following steps: by mass, the modified hard carbon precursor, biomass-based or resin-based carbon source, phosphorus source, nitrogen source, pore-forming agent and deionized water are mixed and ball-milled or high-speed dispersed for 2-8 hours to obtain a phosphorus source composite coating slurry; the phosphorus source composite coating slurry is dried and placed in a nitrogen or argon atmosphere and heat-treated at 550-850℃ for 1-4 hours to obtain the phosphorus-coated hard carbon material.

8. A phosphorus-coated hard carbon material according to claim 7, characterized in that, The drying method of the phosphorus source composite coating slurry is one of spray drying, vacuum drying, forced air drying or freeze drying; When using spray drying, the inlet air temperature is 150-210℃, the outlet air temperature is 75-115℃, and the atomizing disc rotation speed is 8000-18000 r / min; When vacuum drying or forced air drying is used, the drying temperature is 60-120℃ and the drying time is 6-24h.

9. A sodium-ion battery negative electrode sheet, characterized in that, The sodium-ion battery negative electrode sheet includes a current collector and a negative electrode active material layer disposed on at least one side of the current collector. The negative electrode active material layer includes the phosphorus-coated hard carbon material as described in claim 1, a conductive agent, and a binder. By mass percentage, the negative electrode active material layer includes 80-96 wt% phosphorus-coated hard carbon material, 1-10 wt% conductive agent, and 2-10 wt% binder.

10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The negative electrode is the sodium-ion battery negative electrode as described in claim 9. When the phosphorus-coated hard carbon material is used as the negative electrode material for the sodium-ion battery, it can provide sodium-ion insertion / extraction channels through a hard carbon matrix with a layer spacing of 0.35-0.42 nm, allowing for the insertion / extraction of sodium ions through a 1-50 nm layer spacing. 2 The specific surface area of ​​ / g reduces electrolyte side reactions, enhances the interfacial bonding between the phosphorus coating and the hard carbon matrix through oxygen- or nitrogen-containing functional groups, and improves the cycle stability and rate performance of the anode material through the phosphorus coating.